Spatial and Temporal Analyses of Bobwhite Hunting Dynamics - D.Abraham Woodard; Leonard A Brennan; Fidel Hernández; Humberto L Perotto-Baldivieso; Neal Wilkins (National Quail Symposium Proceedings, 2022)
A variety of factors influence the harvest of northern bobwhites (Colinus virginianus) and where that harvest occurs on a landscape. Many of these factors can be quantified and manipulated to distribute harvest pressure across time and space to meet desired spring densities. We collected spatial hunting metrics using global positioning system units on trucks and hunting dogs, along with detailed hunting logs from 211 quail hunts during the 2018–2019, 2019–2020, and 2020–2021 statewide hunting seasons in Jim Hogg County, Texas, USA. We found that hunting parties effectively covered 23.8 ± 0.3 hectares per hour, with hunts lasting 3.5 ± 0.1 hours in the morning and 1.7 ± 0.1 hours in the evening. Hunts were less productive during the early season (November–mid-December), with 13% fewer encounters per hour and 31% lower harvest per encounter. We expected daily harvest to increase with hunt velocities, but found no significant relationship with the velocity of either pointing dogs or vehicles. However, as we predicted, total hunting pressure (hunts per 50-meter × 50-meter area) decreased by 12% (range = 7–17) for every 5% increase in brush density and every 10-meter increase in the distance to the nearest access road. Our findings can assist landowners and managers in the distribution of harvest and hunting pressure across properties and hunting seasons.
Keywords: Colinus virginianus; northern bobwhite; bobwhite hunting; quail hunting; hunting variables.